Grain Size Effects on Visible and Near-infrared (0.35–2.5 μm) Laboratory Spectra of Rare Meteorite Classes - K. I. Ridenhour; V. Reddy; A. Battle; D. Cantillo; N. C. Pearson; J. A. Sanchez (The Planetary Science Journal)
Linking near-Earth asteroids to associated meteorites can be a challenging process for many reasons, one being grain size differences. To address this issue for rarer meteorites, we studied visible and near-infrared (0.35–2.5 μ m) reflectance spectra of 11 rare meteorite classes over five different grain size bins (45–90 μ m, 90–150 μ m, 150–300 μ m, 300–500 μ m, and 500–1000 μ m). We analyzed the reflectance properties, diagnostic spectral band parameters (band centers and band area ratios), spectral slope, and taxonomic classification. The spectra were analyzed using principal component analysis to detect trends in principal component (PC) space and the impact on asteroid taxonomic classification in the Bus–DeMeo system. We found that the absolute reflectance (visual albedo) at 0.55 μ m (photometric V band) typically decreases with increasing grain size, although there are some variations such as sharp increases for the slabs. Our EH4 and aubrite show a trend of increasing spectral slope with decreasing grain size. Our ureilite, angrite, winonaite, acapculoite, and mesosiderite show a general trend of a decrease in Band I (∼0.9 μ m) depth with increasing grain size up to 500–1000 μ m. Taxonomic classification of spectra of all grain sizes shows that classification tools generally struggle to differentiate grain size effects from mineralogical variations. This research demonstrates the need for a more robust taxonomic classification system that accounts for grain size and one that accurately classifies small near-Earth asteroids with regolith-free surfaces.